Action of lycopene in prostate cancer: a literature review (Research, Society and Development, 2022)
Introduction: Prostate cancer is the second most common cancer in men. It is a neoplasm focused on the prostate gland. Risk factors are: age over 50 years, genetic factors, eating habits, environmental factors, smoking, alcohol consumption, obesity and African Americans. Carotenoids are compounds that neutralize free radicals and reactive oxygen species. They are found in fruits such as strawberries, tomatoes and papaya. Therefore, the human being is incapable of producing such compounds, being necessary the ingestion of these foods. Lycopene can inhibit the development of cancer cells, decreasing their carcinogenesis through direct mechanisms such as interruption of cell cycles, apoptosis and modulatory signaling. Objective: To investigate the efficacy of the antioxidant action of lycopene on inflammatory and tumor necrosis factors associated with prostate cancer. Methodology: This is an integrative literature review of a descriptive and qualitative nature. Conducted through research platforms such as PubMed and Scielo, books and official websites such as the Instituto Nacional do Câncer and Instituto Oncoguia. Results: 20 articles were selected, 10 of which were experimental, comprising a sample of 288 individuals and 10 systematic reviews and meta-analyses. Conclusion: Lycopene in the men's diet proved to be beneficial. It acts by inhibiting the activation of carcinogenesis, proliferation, angiogenesis, invasion and metastases, blocking tumor cell cycle progression and apoptotic induction through changes in several signaling pathways. However, studies are necessary to better elucidate the bioavailability of lycopene and its mechanism of action in the human body.